Tuberculose em prisões: conhecimento, atitudes e práticas de agentes penitenciários - Colombelli, Fabiana (2018)
Tuberculosis is the single-agent infectious disease that most causes death, surpassing HIV-aids. Among the groups at high risk for tuberculosis are the Persons Deprived of Liberty. Research in this area is directed to the inmates and diseases most frequent in this environment, disregarding the role of the Penitentiary Agent. The objective of this research was to analyze the knowledge, attitudes and practices of those of Penitentiary Agents. This is an exploratory descriptive epidemiological study, from a primary source. The participants answered a questionnaire with open and closed questions of the Knowledge, Attitude and Practice (KAP) model. The answers were typed (double typing) in a spreadsheet, the Kappa coefficient of agreement was 0.904. The data were analyzed in Statistica 12.0 StatSoft software. Sociodemographic distribution, characterization of the level of knowledge, practices and attitudes of Penitentiary Agents was performed, which was presented in the form of number and percentage. Analyzes (by means of a contingency table) of the variables of interest were also carried out and according to the variable "previous contact with the tuberculosis theme undergoing training". For this analysis, the distribution according to number and percentage was considered, and the chi-square (χ2) statistical test was used to evaluate the comparative analysis between them, assuming significance level p <= 0.05. Some variables presented significance level of p <= 0.05, as weight loss as a symptom (p = 0.028), insect bite as a form of transmission (p = 0.036), repellent use as prevention (p = 0.020), and active search of the respiratory symptomatic as a priority action within the penitentiaries (p = 0.006). There was a relationship between knowledge with age, schooling, time of profession as Penitentiary Agent, participation in courses and assistance to the detainee with tuberculosis, and that the approach to illness in training courses was not significant at the level of knowledge. It was concluded that there is a need for investments in the education of these agents, suggesting Permanent Education as a tool to improve the knowledge of this team.